2021
DOI: 10.1007/s10965-021-02740-6
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating doxycycline loading and release performance of imprinted hydrogels with different cross-linker concentrations: a computational and experimental study

Abstract: Effective non-covalent molecular imprinting on a polymer depends on the extent of non-bonded interactions between the template and other molecules before polymerization. Here, we first determine functional monomers that can yield a doxycyclineimprinted hydrogel based on the hydrogen bond interactions at the prepolymerization step, revealed by molecular dynamics (MD) simulations, molecular docking, and simulated annealing methods. Then, acrylic acid (AA)-based doxycycline (DOX) imprinted (MIP) and non-imprinted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Several studies with the aim to explain the molecular basis of recognition have demonstrated the significance of including all the polymer building blocks in the simulation by illuminating the nature of complex formation and underlying mechanisms [53,54,[160][161][162][163][164][165][166][167][168][169]. Some strategies involved the evaluation of the choice of suitable polymer components such as the type of functional monomer, crosslinker, template or porogen [170][171][172][173][174][175][176] and/or the investigation of the relative stoichiometries between the monomers [172,[175][176][177][178][179][180][181][182][183][184][185][186][187][188] suitable for use in imprinting protocols. A recent example by Rebelo et al [183] reported the development of a MIP-based electrochemical sensor, comprised of a carbon paste electrode modified with MIP microparticles and multi-walled carbon nanotubes, for detection of the antibiotic furazolidone in environmental waters.…”
Section: (A) (B)mentioning
confidence: 99%
“…Several studies with the aim to explain the molecular basis of recognition have demonstrated the significance of including all the polymer building blocks in the simulation by illuminating the nature of complex formation and underlying mechanisms [53,54,[160][161][162][163][164][165][166][167][168][169]. Some strategies involved the evaluation of the choice of suitable polymer components such as the type of functional monomer, crosslinker, template or porogen [170][171][172][173][174][175][176] and/or the investigation of the relative stoichiometries between the monomers [172,[175][176][177][178][179][180][181][182][183][184][185][186][187][188] suitable for use in imprinting protocols. A recent example by Rebelo et al [183] reported the development of a MIP-based electrochemical sensor, comprised of a carbon paste electrode modified with MIP microparticles and multi-walled carbon nanotubes, for detection of the antibiotic furazolidone in environmental waters.…”
Section: (A) (B)mentioning
confidence: 99%
“…Hydrogel systems have been broadly used in the development of delivery systems for drugs [17,18] and protein [19]. Because of their hydrophilic structure [10], natural polysaccharides in hydrogel form such as chitosan [6,20,21], alginate [10,22], starch [23], hyaluronic acid, and pectin [24] have been widely used in the fabrication of dressings for burned, exuding, and bleeding wounds.…”
Section: Introductionmentioning
confidence: 99%